(untitled) (Academic Journal of Internal Affairs, 2025)
Aim: The aim of the study is to present the currently known challenges of presentation attacks against biometric systems, their law enforcement and national security aspects, and to draw attention to the importance and possibilities of solutions and devices that provide different levels of security in system design and biometric identity verification, and their limitations, to regular and target-oriented risk analysis. Methodology: The study presents the results of the latest research on presentation attacks, by processing the professional publications, studies, test reports, reports of leading international organizations, and by reviewing the solutions provided by existing standards, it presents the attacks against biometric systems and draws conclusions. Findings: Biometric systems are systems using artificial intelligence technologies, they have enormous advantages and the opportunities provided by the technology, and, of course, parallel to this, the challenges arising from the technology and the tasks to be solved. The threats arising from the use of technology for bad purposes, the deception of biometric systems are a real, increasingly challenging problem, and the recognition and prevention of forgery and deception is not yet easy due to the complexity of the task. Extensive research is currently being carried out in this area, but it has been established that there is no generally usable solution or tool or application that can be integrated into the systems to protect against such threats. Technical solutions and tools help, but only with a risk-based approach, setting up risk levels and corresponding system design and thoughtful security policy measures, false data communications and attacks deceiving biometric systems can be successfully recognized and prevented or the damage mitigated. Value: Knowledge of the challenges of automatic identity verification technology and current methods of deceiving biometric systems is the basis for planning defense methods and procedures, and is also in the interest of law enforcement and national security. The article aims to provide support for this with the analysis.